2018
DOI: 10.1186/s12872-018-0897-y
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective cohort study to develop frailty-based prognostic criteria in heart failure patients (FLAGSHIP): rationale and design

Abstract: BackgroundHeart failure (HF) and frailty often co-exist, and frailty in HF results in a poor prognosis. However, in Asian populations, prognostic criteria are needed to examine the effect of frailty on HF. Therefore, we conducted a nationwide cohort study to develop frailty-based prognostic criteria in HF patients (FLAGSHIP). FLAGSHIP mainly aims to 1) develop the frailty criteria based on HF-specific outcomes, 2) propose a hypothesis of the potential mechanisms of frailty manifestations in HF, and 3) examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
(33 reference statements)
0
24
1
1
Order By: Relevance
“…Previous studies have shown some predictors of functional decline after HF [ 7 , 20 22 , 24 ]. While those studies examined risk factors for functional disability, their timing of assessment differed from our study, that is, while previous studies were conducted on hospital admission and/or at discharge, we gathered information on risk factors in subjects initially free of diseases and identified etiologic precursors by following up for 11 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown some predictors of functional decline after HF [ 7 , 20 22 , 24 ]. While those studies examined risk factors for functional disability, their timing of assessment differed from our study, that is, while previous studies were conducted on hospital admission and/or at discharge, we gathered information on risk factors in subjects initially free of diseases and identified etiologic precursors by following up for 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for HF have been well established in a previous cohort study [ 19 ]. Some studies have assessed functional disability using frailty [ 20 , 21 ], ADL [ 7 ], and muscle strength [ 22 ] after HF. Studies have identified risk factors for the development of disability in patients with HF [ 7 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…People with unfavorable social status Table 3 Hazard ratios for functional disability among the self-rated health groups excluding participants with sub-clinical and severe cases and unhealthy status might conceive their health as being poor, which consequently lead to be functional disability. CV diseases are well-known risks for future functional disability [38][39][40][41]. The main reasons for receiving LTCI were cerebrovascular disease (stroke) (21.5%) followed by dementia (15.3%) [42].…”
Section: Discussionmentioning
confidence: 99%
“…CV diseases are well-known risks for future functional disability [ 38 41 ]. The main reasons for receiving LTCI were cerebrovascular disease (stroke) (21.5%) followed by dementia (15.3%) [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low physical strength in elderly patients who are at risk of becoming frail must be addressed (15). The present study showed that the exercise capacity at AT was maintained by continuous CR for up to five years.…”
Section: Discussionmentioning
confidence: 99%